2020
DOI: 10.21203/rs.3.rs-70471/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in Depression and Physical Activity Among College Students on a Diverse Campus After a COVID-19 Stay-at-Home Order

Abstract: The numerous negative health impacts of COVID-19, which include expected changes to psychiatric illness and physical activity (PA), are disproportionately distributed in the United States. Mental illnesses and physical inactivity are prevalent among U.S. college students. This study examined whether there was a change in minutes of PA and depression scores after a stay-at-home order and examined predictors of these changes. An online survey was sent to all undergraduate and graduate students attending a large,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Almost in every fifth person the level of physical activity was estimated as high. Similar results regarding the limitation and low level of physical activity were noticed among students during the pandemic in England [ 22 ], Scotland [ 23 ], Italy [ 24 ], Spain [ 25 ], Switzerland [ 26 ], Hungary [ 27 ], USA [ 28 ], Mexico [ 29 ] and China [ 30 ]. A decrease in the level of physical activity among students of physiotherapy was observed in India, where its level was defined as medium [ 31 ].…”
Section: Discussionsupporting
confidence: 61%
“…Almost in every fifth person the level of physical activity was estimated as high. Similar results regarding the limitation and low level of physical activity were noticed among students during the pandemic in England [ 22 ], Scotland [ 23 ], Italy [ 24 ], Spain [ 25 ], Switzerland [ 26 ], Hungary [ 27 ], USA [ 28 ], Mexico [ 29 ] and China [ 30 ]. A decrease in the level of physical activity among students of physiotherapy was observed in India, where its level was defined as medium [ 31 ].…”
Section: Discussionsupporting
confidence: 61%
“…The level of depression shown in Table 1, health students who experienced a low level of depression was 25.6% and a severe depression level was 7.3%. In a study by Coughenour et al (2020), it was shown that the policy Stay at Homemade the level of depression in healthy students increased. Higher than before the policy was implemented (average before: 5.58, and after 9.61) [13].…”
Section: Resultsmentioning
confidence: 99%
“…In a study by Coughenour et al (2020), it was shown that the policy Stay at Homemade the level of depression in healthy students increased. Higher than before the policy was implemented (average before: 5.58, and after 9.61) [13]. Pandey et al also found that more depression levels were experienced by female students compared to male students (5 vs. 3, p = 0.025) [11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations